Effect of Storytelling on Listening Skills and Vocabulary of Preschool Children - Maryam Ahmed, Attiya Inam, Jahanara Saif (JECCE, 2023)
Storytelling has been used as the oldest form of learning. Even though for years, storytellers shared stories with children, up till now very few researches have been conducted on impact of storytelling on children’s learning. The current research was an effort to explore the effect of storytelling on listening skills and vocabulary of preschool children. This study was a quasi-experimental design. The total sample comprised of 14 participants of preschool children aged 5 years divided in 2: control (n=7) and experimental (n=7) groups through non-random sampling. The data was collected and assessed by means of globally recognized scales Morrow’s Retelling 10 Point Scale for listening skills and Vocabulary Knowledge Scale (VKS) for vocabulary. Six stories were selected for storytelling; first story for pre-test, four stories for interventions and sixth story for post-test story telling. The statistical analysis was done by conducting independent samples t-test and paired samples t-test to compare scores among control and experimental groups. The post-test results and the researcher observations affirmed that preschool children who were exposed to storytelling with props were highly engaged in story retelling; incorporating minute details which verified listening attentively and carefully maturing their listening skills and revealed better, meaningful, and deeper understanding of vocabulary